2007
DOI: 10.1007/s00406-007-0737-z
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholism in women: is it different in onset and outcome compared to men?

Abstract: Onset and course of alcohol dependence show gender related differences (telescoping effect) suggesting that women are more vulnerable to chronic alcohol consumption. This raises the question whether the differences are associated with a different treatment outcome as well. We hypothesized, that alcohol dependent women with a telescoping course show a less favourable treatment outcome compared to men. We investigated 212 alcohol dependent patients; matching 106 consecutively admitted women with 106 men drawn fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
4
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 47 publications
8
67
4
2
Order By: Relevance
“…The initial report of telescoping considered the onset and time course of alcohol dependence in men and women in a treatment program. This has been replicated a number of times, although not all studies have found evidence of greater telescoping in a treatmentseeking population of women compared with men (for a summary, see Diehl et al, 2007).…”
Section: Sex Differences In Drug Abusementioning
confidence: 82%
“…The initial report of telescoping considered the onset and time course of alcohol dependence in men and women in a treatment program. This has been replicated a number of times, although not all studies have found evidence of greater telescoping in a treatmentseeking population of women compared with men (for a summary, see Diehl et al, 2007).…”
Section: Sex Differences In Drug Abusementioning
confidence: 82%
“…Potentially influential predictors of progression to alcohol-related harm besides alcohol consumption include socioeconomic position (SEP) [24, 25], early age of alcohol initiation [26], being male (although females appear to suffer serious negative consequences of alcohol consumption earlier and to a greater degree than men) [27, 28], family history [29], comorbid substance use, with alcohol use increasing the risk for other drug use disorders [30, 31], poor physical and mental health [32], sex differences [33, 34], and ethnicity [35]. The adverse effects of alcohol drinking behavior affect not only the index drinker but also family members of the drinker [36] and the society as well.…”
Section: Introductionmentioning
confidence: 99%
“…Although AUD may be less prevalent among women, women with AUD may suffer more adverse consequences than men as a result of their drinking. Women with AUD are shown to exhibit a later onset of AUD, and more quickly progress to serious AUD problems (Diehl et al., 2007). In comparison to men who are heavy drinkers, women who are heavy drinkers are prone to exhibit serious medical problems, such as liver cirrhosis (Rehm et al, 2010), and have higher mortality rates (Jacques-Lopez et al, 2001).…”
mentioning
confidence: 99%